Efficacy of Risk Factors Management on Decreasing Systolic Blood Pressure Level in Hypertensive Patients at Bang Yai Hospital, Nonthaburi - Changpradub, Wichanyudh (Journal of Health Science of Thailand, 2017)
This quasi-experimental study was designed to evaluate a decrease of systolic blood pressure(SBP) in 86 new hypertensive patients at Bang Yai hospital during January 2007 - June 2008. Ofwhich, 32 were advocates of risk factors control program and 54 underwent normal treatment proce-dure. Descriptive statistics were employed. Comparisons of average levels of SBP of the two groupswere made using independent sample t-test and differences between pre-post average levels of SBPof each group were established by dependent sample t-test. Correlations between the body massindex and the levels of SBP were established by Pearson’s correlation coefficient. Associationsbetween the nutritional control and the levels of SBP was tested by independent sample t-test. It wasfound that the experimental group showed significant reduction of SBP (p < 0.001) whereas theopposite trend was witnessed in the control group (p < 0.001). Significant associations betweenDASH diet program or aerobic exercise (≥30 minute/day) with SBP levels were reported (p <0.001). The results confirms the effectiveness of the risk factors control program in reducing SBPlevels in the patients and the measure should be complementary to the normal treatment procedure.